2018
DOI: 10.1021/acs.macromol.8b00599
|View full text |Cite
|
Sign up to set email alerts
|

Recombination Strategy for Processable Ambipolar Electroactive Polymers in Pseudocapacitors

Abstract: In order to circumvent the contradiction between processability and electrochemical performances, we report a recombination strategy in both unit and segment scales for processable ambipolar electroactive materials starting from parental moieties: classic ambipolar polymer (PEBE) and its soluble analogue (PPBP). On the basis of this strategy, two recombined polymers (PEB-P and PEBE-PBP) are successfully prepared via direct (hetero)­arylation copolymerization. Through systematical characterization of properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Compared with conventional supercapacitor electrode materials, like transition metal oxides, , conductive polymers have the advantages of flexible design, easy synthesis, low cost, and good conductivity. Donor–acceptor–donor (D–A–D) building blocks as a kind of typical conjugated conductive polymer has been widely reported in the field of electrochromism because of its tunable band gap, also studied in capacitance with fantastic attraction due to the wide potential range, such as exhibited by the involvement of a donor unit 3,4-ethylenedioxythiophene (EDOT). Recently, the applications of D–A–D type materials in ESCs have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with conventional supercapacitor electrode materials, like transition metal oxides, , conductive polymers have the advantages of flexible design, easy synthesis, low cost, and good conductivity. Donor–acceptor–donor (D–A–D) building blocks as a kind of typical conjugated conductive polymer has been widely reported in the field of electrochromism because of its tunable band gap, also studied in capacitance with fantastic attraction due to the wide potential range, such as exhibited by the involvement of a donor unit 3,4-ethylenedioxythiophene (EDOT). Recently, the applications of D–A–D type materials in ESCs have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…The optimal configuration for a polymer-based supercapacitor device would consist of two electrodes made from a single ambipolar polymer capable of stably storing both positive and negative charges, known as a type III device. , However, suitable ambipolar materials are rare, usually exhibiting relatively poor stability for negative charge storage. Recent progress on donor–acceptor π-conjugated polymers has shown that it is possible to improve negative charge storage stability by introducing electron-withdrawing groups, but this results in a corresponding reduction in positive charge storage performance. It is thus beneficial to isolate positive and negative charge storing units in order to maintain the individual performance of each. Qin et al synthesized a donor–node–acceptor polymer, consisting of a dicarbazole donor unit and a tetrachlorinated perylene diimide (PDI) acceptor unit .…”
Section: Introductionmentioning
confidence: 99%